KELUARGA KORBAN KEKERASAN TERHADAP ANAK DI KECAMATAN BENGKALIS - Handris, Tri; ", Risdayati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2021)
This research was conducted in the Bengkalis sub-district, Bengkalis district. The purpose of this study was to describe the family background of victims of child abuse in Bengkalis District. As well as to find out some conditions that occur in the families of victims of this violence. The research subjects or respondents involved in this study amounted to 1 child psychologist companion in the Bengkalis sub-district and 4 parents of child abuse victims in the Bengkalis district. This study used a qualitative descriptive approach. The main data collection tool is from the Bengkalis District Office of Child and Women's Protection, because researchers advise that it is the main instrument in the field. Respondents were selected based on their ability and openness to effective data seekers. The methods used are observation, documentation and in-depth interviews. Data checking from various sources was carried out through technical triangulation in an effort to increase the researchers' understanding of what had been found. From the results of this research, it shows that there are several factors that cause a child to become a victim of violence, namely: (a) Relationships in the Family (b) Family Function (c) Family Roles. Families of violence victims have low economic capacity Keywords : Parents Of Victims Of Child Abuse, Family Function, Family Relationships